Digital Engineering Strategy to Enable Enterprise Systems Engineering. Issue 1 (30th September 2020) - Noguchi, Ryan A.; Wheaton, Marilee J.; Martin, James N.
Abstract: As defined in the U.S. Department of Defense (DoD) Digital Engineering (DE) Strategy, DE is "an integrated digital approach that uses authoritative sources of system data and models as a continuum across disciplines to support lifecycle activities from concept through disposal." This DoD DE Strategy establishes a set of goals and objectives for DE within the DoD. This paper provides an elaboration of that strategy for organizations who seek to apply DE not only for the improvement of program and project outcomes, but to achieve a more efficient and effective implementation of enterprise systems engineering (ESE) to improve enterprise outcomes. The paper then describes the roles and responsibilities needed for the effective and efficient implementation of DE principles and concepts in support of the systems engineering activities across the enterprise to facilitate the disciplined exercise of ESE at every organizational level.